Are There Any Differences in the Prognostic Value of Left Ventricular Ejection Fraction in Coronary Artery Disease Patients With or Without Moderate and Severe Mitral Regurgitation? - Li, Qiang; Zhang, Yifei; Huang, Haozhang; Chen, Weihua; Shi, Shanshan; Chen, Shiqun; Wang, Bo; Lai, Wenguang; Huang, Zhidong; Luo, Zhiling; Chen, Jiyan; Tan, Ning; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Left ventricular ejection fraction (LVEF) is a vital variable to describe left ventricle systolic function and contractility of left ventricle. However, the association between LVEF and the prognostic effect in patients with moderate or severe mitral regurgitation (MR) is still controversial. Methods: This study comprised 30,775 coronary artery disease (CAD) patients who underwent coronary arteriography (CAG) in the Cardiorenal ImprovemeNt (CIN) registry from January 2007 to December 2018. Patients were divided into none or mild MR group and moderate or severe MR group, and 3 levels of LVEF ≥ 50%, 40% - 50% and < 40% were further distinguished according to hospital baseline. Univariate and multivariate Cox proportional analyses were used to investigate the association between LVEF levels and long-term all-cause mortality in patients with different MR severity. Results: Of 30,775 CAD patients (62.9±10.6 years, female 23.8%), 26,474 (86.0%) patients had none or mild MR. Compared with none or mild MR patients, patients with moderate or severe MR were older and had worsen cardio-renal function. On multivariable Cox proportional analysis, LVEF < 40% was independently associated with higher mortality regardless of MR severity [none or mild MR (adjusted HR: 1.79; 95% CI: 1.56-2.05, P < 0.001), moderate or severe MR (adjusted HR: 1.57; 95% CI: 1.29-1.91, P < 0.001)] compared with LVEF ≥ 50%. Conclusions: LVEF is a reliable prognostic index in CAD patients, even in those with moderate or severe MR. LVEF monitoring would still be clinically useful in CAD patients with moderate or severe MR. Clinical trials are needed to prospectively evaluate the optimal threshold for LVEF in patients with moderate or severe MR.